Effect of extended application time of universal adhesives on bond strength of brackets and enamel integrity (Research, Society and Development, 2021)
The objective of this study to evaluate the effect of universal adhesives application time to enamel through shear bond strength (SBS), adhesive remnant index (ARI), and morphological enamel integrity. Bovine incisors were divided into four groups according to bonding system protocol (n=20): (1) conventional etch-and-rise adhesive – Transbond XT Primer (P-XT); (2) one-step self-etching adhesive – Transbond Self Etching Primer (T-SEP); (3) one universal adhesive – Single Bond Universal, which were rubbed for 20s (SBU-20) or (4) 40s (SBU-40). Transbond XT composite was used to bond the brackets to enamel. SBS was evaluated in a universal test machine at 0.5mm/minute. ARI was determined under x12.5 magnification and enamel damage was evaluated through scanning electron microscope (SEM) after debonding (n=10). SBS data were compared using one-way ANOVA and Tukey’s test. The Kruskal–Wallis test was used to compare the ARI scores (α =0.05). The P-XT and T-SEP groups showed significantly higher bond strength than SBU-20 and SBU-40 (p0.05). SEM showed enamel damage only in T-SEP and P-XT groups. Conventional ‘etch and rinse’ and ‘self-etch’ adhesives had the highest shear bond strength, but they were associated with more enamel damage compared to universal adhesives. The application of universal adhesives with the time recommended by the manufacturer — ensure satisfactory bond strength and enamel integrity.